Development of Suitable Groundnut Genotypes for Summer Season Under Climate Change and to Food and Nutritional Security (British Journal of Multidisciplinary and Advanced Studies, 2022)
The present study was under taken during summer seasons of 2007 and2008 at Regional Research Station, Mainpuri. The experimental soil was sandy loamwith poor fertility status. The main objective was to find out the suitable genotypes forcultivations during summer season with suitable physiological parameters. The twentyvarieties of groundnut i.e. Dh86, Dh40, R9251, R8808, R2000-1, ICGS44, ICGS1,ICGS37, ICGS11, ICGS76, ICGV93468, ICGV86590, ICGV86325, ICGV00310,ICGV00298, ICGV99195, ICGV02099, ICGV02022, ICGV94361 and G201 (check)were tested for evaluating the suitable physiological parameters during summerseason. The sowing was done in rows 30 cm apart with 10 cm plant spacing. Seed wasseeded on 10 March, 2007 and 2008 and harvested after 90 days of sowing duringboth the experimental years. Cultivars Dh 86 (29.02 q/ha) and ICGV93468 (28.91q/ha) gave highest pod yield, while genotypes Dh40 and G201 gave minimum podyield. The increase or decrease in pod yield (q/ha) was due to increase or decreasein number of pod per plant, pod weight per plant, number of kernel per plant, weightof kernels per plant, number of kernel per pod, kernel weight per pod, weight of 100-kernel, dry matter accumulation in pods and harvest index. The better source-sinkrelationship was also responsible for higher pod yield. The aforementioned growthand yield contributing characters were found superior in Dh86 and ICGV93468 insummer season, resulted in, both cultivars gave highest yield under summer season inU.P. The important physiological parameters were found in favour of Dh86 andICGV93468 in increasing the pod yield during summer season cultivation.